Promoting uncommon use of knowledge in information system departments: The role of human resource management practices. Issue 5 (1st October 2018) - Wang, Shih-Yu; Hsu, Jack Shih-Chieh; Li, Yuzhu; Lin, Tung-Ching
Abstract : Purpose: The purpose of this paper is to gain a clear understanding of the impact of uncommon use of knowledge (adaptation and augmentation) on the performance of information systems (IS) departments, and to explore the effects of human-resources management (HRM) practices on uncommon use of knowledge. Design/methodology/approach: A questionnaire-based survey was used to measure the constructs of the research model. A survey package was delivered to project managers or team leads and 133 responses were returned. Findings: The empirical results indicate that knowledge adaptation has a significant effect on departmental performance, whereas knowledge augmentation is more important to innovation than to routine departmental performance. The results also show that, while knowledge adaptation can be enhanced by communication and an uncertainty-avoidance culture, knowledge augmentation is an outcome of shared decision-making, the use of teams, and innovation-based policies. Research limitations/implications: Given the positive impact of uncommon use of knowledge on IS department performance, future research should explore other factors besides HRM practices to boost it. Practical implications: The results can serve as guidance for managers looking to select HRM practices to promote uncommon use of knowledge. Originality/value: This study introduces knowledge adaptation and knowledge augmentation as the component processes of uncommon use of knowledge to the IS discipline, and empirically validates the antecedents and consequences of uncommon use of knowledge using survey data.